PENGARUH TERAPI MUROTTAL TERHADAP TINGKAT HIPERAKTIF – IMPULSIF PADA ANAK ATTENTION DEFICIT HYPERACTIVE DISORDER (ADHD) - Fithroh Roshinah Roshinah; Laila Nursaliha; Saiful Amri (Pelita - Jurnal Penelitian Mahasiswa UNY, 2014)
The research is aimed at revealing the murottal therapy process given to ADHDchildren and to find out the effect of the therapy on the hyperactive-impulsive behavioursof the ADHD children. The method employed in this research is Subject SingleResearch (SSR) method using the A-B-A design. The subjects of the reasearch are thethird grade students of a special school. The data were collected through observations.The research findings show that the murottal therapy cann reduce the hyperactivityand impulsiveness level among the ADHD children. Such a theraphy positively affectsthe calmness condition of the ADHD children.